Business sustainability model of smallholder layer farms in Kendal Regency, Central Java, Indonesia - Sofyan, A.; Suprijatna, E.; Santoso, S. I.; Setiadi, A. (Diponegoro University, 2019)
This study was aimed to analyze factors and models of business sustainability of smallholder layer farms in Kendal Regency, Indonesia. Purposive sampling method was used to select 120 active layer chicken farmers in Sukorejo, Pageruyung, Patean, Limbangan, and Boja Districts as research respondents with the ownership of 300 to 10,000 birds. Research variables consisted of three external variables (social, economic, and institutional) and two internal variables (income and business sustainability). Closed questionnaires were used to collect data. The data were analyzed descriptively using Structural Equation Modeling (SEM) by AMOS 21 software. The results showed that the exogenous and endogenous variables met the modeling criteria with Chi square value = 160.764; probability = 0.380; CMIN / DF = 1.031; GFI = 0.892; AGFI = 0.841; TLI = 0.998; CFI = 0.998; RMSEA = 0.016. Social, economic, institutional and income variables had a significant and positive influence (P≤0.05) on business sustainability. The constructed model had a strong and positive relationship, so it could illustrate the sustainability model of layer business in Kendal Regency.